FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT PERAWAT DI RUANG RAWAT INAP DAHLIA A RSUD RAJA AHMAD THABIB TANJUNGPINANG - Cynthia Hardivianty; Dea Muspratiwi; Samira Samira (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Nurse is a line future of health care plays an important role in the face of the patient's health problems for 24 hours continuously. Nurse is a group of health workers who are at risk of Burnout. This study aims to determine and identify the factors associated with burnout nurses in a hospital inpatient Dahlia Raja Ahamd Thabib Tanjungpinang. This research uses design descriptive analytic with approach. cross sectional The population in this research that nurses working in patient wards Dahlia A total of 17 people. Sampling was done by sampling saturated. The research instrument was a questionnaire. The results of the analysis of data processing using the test Spearman Rho showed that there is a relationship between role ambiguity with burnout of nurses with a value of ρ value = 0,001, there is a relationship between role conflict with burnout of nurses with a value of ρ value = 0.004, there is a relationship between workload with burnout nurse with a value of ρ value = 0.029, there is no relationship between social support and burnout of nurses with a value of ρ value = 0.223. It is expected that nurses try to implement measures that allow the avoidance of saturation works as follow relaxation exercises once a week, eat healthy and nutritious